2016
DOI: 10.1590/0100-67622016000300012
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hymenaea Courbaril Seedlings in Function of Containers and Irrigation Blades

Abstract: -The objective of this work was to evaluate the effect of container sizes and irrigation levels on "jatoba" (Hymenaea courbaril L.) seedlings development. The experiment was conducted in a greenhouse from September 2010 to March 2011. The design was in randomized blocks, with three replications in split plots, in a 2 x 5 scheme. Two container sizes (rigid pots of 3.1 L and stiff plastic tubes of 4.0 L) were used in the plots, while five drip irrigation levels (20%, 40%, 60% 80% and 100% of potential evapotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…These results indicate that water deficits can severely affect growth and fresh and dry biomass accumulation in plants (Silva et al, 2016). Jeromine et al (2019) observed that seedlings with greater root dry weights probably have greater chances of surviving water-stress during the dry season in the natural environment, and this characteristic is therefore extremely important for the successful growth of seedlings.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…These results indicate that water deficits can severely affect growth and fresh and dry biomass accumulation in plants (Silva et al, 2016). Jeromine et al (2019) observed that seedlings with greater root dry weights probably have greater chances of surviving water-stress during the dry season in the natural environment, and this characteristic is therefore extremely important for the successful growth of seedlings.…”
Section: Discussionmentioning
confidence: 88%
“…It is observed in the literature that, for overcoming the water deficit stress, plants invest in root biomass with reduction of leaf expansion and, consequently, reduced consumption of carbon, being observed reductions in the growth of shoots (Carvalho et al, 2012. ), leaf area (Jeromine et al, 2019;Mar et al, 2013;Scalon et al, 2011) and increased ratio of root biomass and shoot (Silva et al, 2016;Verma et al, 2012). However, this behavior was not observed in T. roseoalba seedlings, probably due to the assessed stage of development or the period in which they remained in culture conditions Plant responses to soil water conditions are quite variable, but tree species tend to attain greater heights and diameter as soil-water becomes more available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seedlings of Hymeneae. courbaril L. develop better in irrigation depths from 90 to 100% of potential evapotranspiration, and the water deficit reduces the height, diameter, leaf area and shoot dry mass of the seedlings (SILVA et al, 2016). Seedlings of Campomanesia adamantium and Hancornia speciosa also grow better when grown in 75% and 100% of WHC; however cultivation under water restrictions (25% and 50% WHC) causes growth reduction GORDIN et al, 2016).…”
Section: Discussionmentioning
confidence: 99%